Influence of social-normative information on the modeling of food-related decisions. (1st September 2022) - Rubenstein, Sarah A.; Vartanian, Lenny R.; Herman, C. Peter; Polivy, Janet
Abstract: Social modeling is a powerful influence on people's food intake: When there is a clear and consistent norm, people eat more when eating with someone who eats a lot and eat less when eating with someone who eats only a little. In three studies, the present research examined how clear versus ambiguous social-normative information influences the modeling of food-related decisions. Using a novel online decision-making paradigm, female participants (total N = 1042) were provided with information about how many cookies previous participants had supposedly selected (no information was provided in the control condition), and then decided how many cookies they would choose for a snack. When there was a clear and consistent norm, the typical social modeling effect was observed. When there was a small number of "dissenters" whose responses conflicted with the norm set by the majority, participants' cookie selection still conformed to the behaviour of the majority (Studies 1 and 2). It was only when the behaviour of the previous participants was highly ambiguous that participants behaved as if they had been given no normative information (Study 3). By demonstrating that, except in extreme cases, people use the available information to discern a social norm that influences their behaviour, these findings highlight the power of social norms related to food-related decisions.